A luminance-based heart chip assay for assessing the efficacy of graft preservation solutions in heart transplantation in rats. Issue 1 (17th January 2013) - Maeda, Masashi; Kasahara, Naoya; Doi, Junshi; Iijima, Yuki; Kikuchi, Takeshi; Teratani, Takumi; Kobayashi, Eiji
Abstract : Objective: We developed a novel luciferase-based viability assay for assessing the viability of hearts preserved in different solutions. We examined whether this in vitro system could predict heart damage and survival after transplantation in rats. Design: By our novel system, preserved heart viability evaluation and transplanted heart-graft functional research study. Setting: University basic science laboratory. Interventions: Isolated Luciferase-transgenic Lewis (LEW) rat cardiac-tissue-chips were plated on 96-well tissue-culture plates and incubated in preservation solutions at 4°C. Viability was measured as photon intensity by using a bio-imaging system. Heart-grafts preserved in University of Wisconsin (UW), extracellular-trehalose-Kyoto (ETK), Euro-Collins (EC), histidin-tryptophan-ketoglutarat solution (HTK), lactated Ringer's (LR) or normal saline solution were transplanted cervically by using a cuff-technique or into the abdomens of syngeneic wild-type LEW rats by using conventional microsurgical suture techniques. Main outcome measures: Imaging an evaluation of preservation heart-graft and functional analysis. Results: Cardiac-tissue-chips preserved with UW, HTK or ETK solution gave higher luminance than those preserved with EC, LR or normal saline (p<0.03). After 24 h of preservation of hearts in each solution at 4°C, the beating of the isolated hearts was evaluated. The success rate, evaluation of beating, of cervical heart transplants using UW and ETK solution exceeded 70%, but those using other preservation solutions were lower (UW: 100%, ETK: 75%, EC: 42.86%, HTK: 14.29%, normal saline: 0%). Histological analysis of cervical heart-grafts after 3 h preservation by myeloperoxidase (MPO), zona occludens-1(ZO-1), and caspase-3 immunostaining revealed different degrees of preservation damage in all grafts. Conclusions: Our novel assay system is simple and can test multiple solutions. It should therefore be a powerful tool for developing and improving new heart-graft preservation solutions.